Bisphenol AF: Halogen bonding effect is a major driving force for the dual ERα-agonist and ERβ-antagonist activities. Issue 3 (1st February 2020) - Liu, Xiaohui; Suyama, Keitaro; Shiki, Junichi; Torikai, Kohei; Nose, Takeru; Shimohigashi, Miki; Shimohigashi, Yasuyuki
Graphical abstract: Highlights: BPE-X, bisphenol E analogs containing CX3 (CF3 or CBr3 ), were newly synthesized. Bisphenol AF (BPAF), BPE-F, BPE-Cl, and BPE-Br were assayed for ERα and ERβ. All these CX3 -bisphenols worked as agonist for ERα, but antagonist for ERβ. The ascending order of both of those activities was BPE-F < BPE-Cl ≤ BPAF < BPE-Br. The electrostatic halogen bonding effect was shown to be a major driving force. Abstract: 17β-Estradiol (E2) is a natural steroid ligand for the structurally and physiologically independent estrogen receptors (ERs) ERα and ERβ. We recently observed that CF3 -containing bisphenol AF (BPAF) works as an agonist for ERα but as an antagonist for ERβ. Similar results were also observed for the CCl3 -containing bisphenol designated as HPTE. Both BPAF and HPTE are comprised of a tri-halogenated methyl group in the central alkyl moiety of their bisphenol structures, which strongly suggests that halogens contribute directly to the agonist/antagonist dual biological functions. We conducted this study to investigate the structure-activity relationships by assessing together newly synthesized CF3 - and CBr3 -containing bisphenol E analogs (BPE-X). We first tested bisphenols for their receptor binding ability and then for their transcriptional activities. Halogen-containing bisphenols were found to be fully active for ERα, but almost completely inactive for ERβ. When we examined these bisphenols for their inhibitory activities for E2 in ERβ, we observed that they worked as distinct antagonists. The ascending order of agonist/antagonist dual biological functions was BPE-F < BPE-Cl (HPTE) ≤ BPAF < BPE-Br, demonstrating that the electrostatic halogen bonding effect is a major driving force of the bifunctional ERα agonist and ERβ antagonist activities of BPAF.